An Improvement on the End-of-Life of High-Speed Rail Rolling Stocks Considering CFRP Composite Material Replacement - Rungskunroch, Panrawee; Kaewunruen, Sakdirat; Shen, Zuo-Jun (Frontiers in Built Environment, 2019)
It is undeniably true that transportation system generates positive impacts on human life but, the using of transportation also emits GHG to the environment that leads to the global warming issue. In the day and age, various technologies have combined with the transportation systems as aiming to reduce the global impact. High-speed rail (HSR), which well-known as low CO2 emission transport, have been continually improved on its model. Regarding this study, the material replacement method is taken to account for a feasibility study on the next model of HSR. There is three types of composite materials consists of glass filled with epoxy, glass filled with polyester and glass filled with nylon replaces on the six chief parts of HSR components. As a result, the total weight of rolling stock has significantly reduced 24.61% on average so, it can reduce the amount of fuel in operation. Also, the feasibility of the recyclability (Rcyc) and recovery rate (Rcov) is critical to judging on the suitability of the replacement. The research found that the replacement of CFRP (Carbon fibre reinforced polymer) generates a positive result on %Rcyc value at 73.9% compared with 61.4% of the original model. Besides, the %Rcov shows at 78.9% higher than 73.1% of the original model.